The Response of Lentil (Lens culinaris Medik.) to Soil Moisture and Heat Stress Under Different Dates of Sowing and Foliar Application of Micronutrients - Venugopalan, Visha Kumari; Nath, Rajib; Sengupta, Kajal; Nalia, Arpita; Banerjee, Saon; Chandran, Malamal A. Sarath; Ibrahimova, Ulkar; Dessoky, Eldessoky S.; Attia, Attia O.; Hassan, Mohamed M.; Hossain, Akbar (Frontiers in Plant Science, 2021)
Soil moisture and air temperature stress are the two major abiotic factors limiting lentil (Lens culi-naris Medik.) growth and productivity in the humid tropics. Field experiments were conducted dur-ing winter seasons (November to March) of 2018–19 and 2019–20 on clay loam soil (Aeric Hap-laquept) of Eastern India to cultivate rainfed lentil, with residual moisture. Our objective was to study the effect of different time of sowing and foliar spray of micronutrients in ameliorating the effect of heat and moisture stress lentil crop experience in its reproductive stage. The study was conducted with two different date of sowing, November and December as main plot treatment and micronutri-ents foliar spray of boron, iron and zinc either alone or combination as subplot treatment. A treatment were no foliar spray was done was given was considered as control. The soil moisture content is de-pleted from 38 to 18% (sowing to harvest) during November sowing; however, in December sowing the depletion is rages from 30 to 15%. The foliar spray of micronutrients helped to have a better can-opy cover and thus reducing the soil evaporation during the later stages of crop growth when the temperature was beyond the threshold temperature of the crop. Crop growth rate (CGR) and biomass were significantly (p≤0.05) higher for November sown crop and with foliar spray of B+ Fe micronu-trients. In the later stages of the crop when the soil moisture started depleting with no precipitation, the canopy temperature increased than air temperature leading to positive values of Stress degree days Index (SDDI). Delay in sowing reduced the duration by 11.4 days (113.5 days vs. 102.1 days) re-sulting in varied accumulated Growing Degree Days (GDD). Foliar spray of boron and iron (FSB+FE) resulted in the highest yield in both years (1436 kg ha-1 and 1439 kg ha-1). The results of the study concluded that the optimum time of sowing and foliar spray of micronutrients may be helpful to alleviate the soil moisture and heat stress for the sustainability of lentil production in the sub-tropical region.